Peak flow reduction from small catchments using smart inlets. Issue 7 (8th August 2020) - Kändler, Nils; Annus, Ivar; Vassiljev, Anatoli; Puust, Raido
ABSTRACT: A concept for reducing stormwater peak run-off from existing small urban catchments is developed. Stormwater inflow from the ground to the pipeline is managed by smart gullies. The gullies are real-time controlled and therefore capable of predicting the weather conditions. Drainage facilities are usually unable to cope with excessive flows that exceed their design limits. This results in pluvial floods and activation of combined sewer overflows, both of which have negative consequences. Northern Europe is expecting to receive more intense rainstorms in the future; therefore, innovative solutions are needed for flow management. The inlet control presented in our work is financially feasible and efficient to be applied to small catchments with substantial permeable surfaces to reduce the peak run-off. The control system is autonomous; therefore, it is suitable for sites scattered around the urban catchment. The concept was successfully tested in a 12 ha catchment area in Tallinn, Estonia.